POSITIVE DEVIANCE PROGRAM DEVELOPMENT TO IMPROVE NUTRITION OF CHILDREN IN MOJOSARI VILLAGE, KALITIDU - Gita Rizki Amaliya (Jurnal Layanan Masyarakat (Journal of Public Services), 2021)
Nutrition is one of the things that is still a global problem, including in Indonesia. Inadequate nutrition from in the womb to birth can cause various health problems for both mother and baby. One of the health problems that can occur in children under five due to malnutrition is stunting. This community service activity was held in Mojosari Village, Kalitidu, Bojonegoro. Undernutrition of children under five is one of the problems that must be addressed by the village government of Mojosari because based on Posyandu data, it was noted that in 2019 there were 38 underfives who were malnourished. The purpose of this community service is as an effort to improve nutrition for malnourished toddlers in Mojosari Village. The community service stages started from problem identification by obtaining primary and secondary data from observations, FGD, indept interviews and questionnaires as well as data from posyandu, ponkesdes and puskesmas. The data then obtained several lists of problems which were then prioritized using the CARL method so that the priority problem was obtained, namely malnutrition. After that, look for the root of the problem using the problem tree diagram, then prioritize alternative solutions using the MEER method. The results of the calculation of the MEER method found the priority alternative solutions, namely the development of the positive deviance (PD) program. So that the community service program carried out is the BOHLAM HATI Program (Providing Processed Healthy Nutritious Food) which contains a series of activities, namely the provision of nutritious food, the innovation of the RAZIA (Children's Nutrition Report) book, socialization in the form of talk shows, cooking demonstrations, and food decoration competitions. This series of activities is expected to increase the participation of mothers and toddlers in the PD program so that it can improve nutrition and reduce the number of under-five malnutrition.